Rethinking sprint breaststroke - McCauley, W.
Why do we breathe every stroke in the 50 and 100 short course breaststroke races? This is the question of this article. One reason only, "coaches" say breathing is part of the biomechanics of the stroke, so why not. That is not good enough for the author ... He starts with the facts derived from scientific research and published by the American Swimming Coaches Association. He thinks that strength work in already strenth athletes can not be the solution, but: What about rethinking the breathing every stroke? Than athor recommends drills for sprint breaststroke technique and fast breaststroke swimming.